O lugar da mulher haitiana na imigração para a Região Metropolitana de Belo Horizonte - Káren Cristina de Fátima Guedes Albino (2019)
After the earthquake that devastated and caused thousands of deaths in 2010 in Haiti, the number of Haitians who had to leave their country and come to Brazil to try a better life has increased considerably. In this context, the Metropolitan Region of Belo Horizonte (RMBH) emerges as an attractive pole for these immigrants due to the networks, places and territories that themselves have constituted in the last decade. On the other hand, throughout this research, I realized that the situation of social integration of Haitian women in the new metropolitan context has been much less intense and effective if compared to Haitian men’s situation. Thus, the general objective of this Master’s dissertation is: to analyze the existing gender relations among the Haitian immigrants living in the RMBH, in order to understand if there have been changes in these relations during the migratory process and fixation of these immigrants in the metropolis, and understand if these changes have allowed the Haitian women to acquire their empowerment, to build their places of emancipation and to conquer their rights in RMBH. To achieve these objectives, I did ethnographic incursions guided by the phenomenological-geographical and Oral History methods.